Strategies for Fostering High School Students' Mental Health Through Counseling Guidance Services - Siregar, Rifani Yasmin Husna; Syarqawi, Ahmad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This research aims to address four research questions based on the background of the problem above, namely: 1) To explain the phenomenon of Guidance and Counseling teachers' understanding of students' mental health problems; 2) To describe the planning and steps of mental health development activities for students carried out by Guidance and Counseling teachers; 3) To elaborate on the evaluation conducted by Guidance and Counseling teachers regarding the development of students' mental health. In this study, the researcher employed a qualitative approach. Data were collected from 5 Guidance and Counseling teachers at Senior High School 6 Pematangsiantar. Data collection techniques used were observation, interviews, and document analysis. Data analysis included data reduction, data presentation, and drawing conclusions. The results of this study indicate that Guidance and Counseling teachers are knowledgeable about and understand what mental health is. The form of mental health development activities designed and implemented by Guidance and Counseling teachers at Senior High School 6 Pematangsiantar by providing information services on 'Mental Health' so that students understand the importance of mental health for themselves. Evaluation conducted by Guidance and Counseling teachers regarding the development of students' mental health at Senior High School 6 Pematangsiantar is carried out through process evaluation and outcome evaluation.